C♯ 2008 and 2005 threaded programming beginner's guide : exploit the power of multiple processors for faster, more responsive software - Hillar, Gastón C. (Packt Pub., 2009)
"This book will guide you through everything you need to start writing multithreaded C♯ applications. You will see how to use processes and threads in C♯, .NET Framework features for concurrent programming, sharing memory space between threads, and much more. The book is full of practical, interesting examples and working code. The book also includes several practical parallelism algorithms and data structures used for illustration, and best practices and practical topics like debugging and performance."--Resource description page